A Coding Scheme for Studying Group Interactions in International Negotiations: A Methodological Advance on the IPA protocol. (25th January 2021) - Dowie, Cheryl; De Bruijn, Oscar; De Mattos, Claudio
Abstract: Our increasingly complex global business environment inevitably brings counterparts to the negotiation table. However, the lack of user‐friendly coding systems, and other associated complexities over the last 6 decades, may have discouraged scholars to further their research in negotiation, communication, and its related fields. A viable coding scheme in place can help scholars and practitioners unfold the negotiation process by explaining the 'cause and effect' relationship within this social context. We propose a 24‐category typology that stems from Bales' IPA model, with Field Theory as our theoretical framework. Our empirical data comprises of two‐party negotiation simulations. Some distinct features of our proposed scheme when compared to the IPA model are reduced coding time experienced, a straightforward framework that is less complicated to follow, a valid and reliable scheme and lastly, a scheme with a robust theoretical‐methodological underpinning in its development. The reliability of our scheme is determined through Krippendorff's Alpha (α). Through our methodological contribution, we aim to investigate the dynamics in small group interactions; and encourage future scholars to study the multidimensional nature of international negotiations.